The Cervical Fat Tissue Volume is a Predictor for Moderate to Severe OSA - Ernst, Glenda; Dalzotto, Pablo; Saban, Melina; Ferraro, Fernando M.; Salvado, Alejandro; Borsini, Eduardo Enrique (Sleep Science, 2023)
Objective Obstructive sleep apnea (OSA) is a disorder characterized by recurrent pharyngeal obstruction during sleep, in which upper airway anatomy plays a key role in its pathogenesis. The aim of this study was to describe whether the quantification of cervical fat tissue volume (CFTV) obtained by Computed Tomography (CT)cephalometry is related to the severity of OSA.Methods Retrospective study between 2018 and 2020 in those patients > 18 years old, with diagnosis of OSA who performed a volumetric cephalometric imaging. Three-dimensional reconstruction of the images was performed and CFTV was measured.Results 91 patients were included in this study of which: without OSA (n: 7), mild (n: 19), moderate (n: 39) and severe OSA (n: 26). We observed a progressive increase of CFTV related to OSA severity has been observed (without OSA: 58.9 ml (47.9-87.5), mild: 59.1ml (48.4-78.3), moderate: 71 ml (42.6-127.1) and severe OSA 103.6 ml (81-153); p < 0.01); nevertheless, no differences were found in the airway volume and neck area. It was showed a significant correlation between CFTV and OSA indicators: AHI, ODI and T90 (Sp r: 0.48; 0.38 and 0.36; p < 0.01 respectively). CFTV cut-off value to discriminate AHI >15 ev/h with best sensitivity-specificity relationship was 64.1 ml with an area under the curve of 0.6 ± 0.06. Multivariate analysis showed that CFTV is a predictor for moderate to severe OSA (OR:3.05, IC95%: 1.14-8.17).Conclusion Cervical fat quantification by CT cephalometry correlates with OSA severity in adults. Fat volume > 64.1 ml increased more than three times the risk of OSA moderate to severe.
Keywords: sleep apnea obstructive; adiposity; cephalometry